Associations of physical activity intensity and specific sedentary behaviors during after-school and weekend with overweight and obesity among preschool children - Ming-Chun Hsueh; Yu-Hsuan Chen (BMC Pediatrics)
Abstract Background This cross-sectional study examined the association between physical activity (PA) intensity and specific sedentary behaviors (SB) among preschool children with overweight or obesity. Methods A sample of 1,115 preschoolers aged 3–6 years in Taipei City was recruited from March to April 2022. Parents completed a validated, self-administered survey assessing the child’s PA intensity (light [LPA], moderate-to-vigorous [MVPA]) and specific SB (total sedentary time [ST], screen-based sedentary time [SST], non-screen sedentary time [NSST], electronic game screen time [EST]). Child’s height and weight were measured, and age- and sex-specific body mass index z-scores were calculated. Logistic regression was used in this study. Results Overall, 23% of the preschool children (age: 4.85 ± 0.91y; 49.9% female) were identified as having overweight or obesity. After adjusting for confounding factors, the highest quartile of total PA, LPA, and MVPA during the weekend was significantly associated with a lower risk of being overweight or having obesity compared with the lowest quartile. Furthermore, the highest quartile of ST and EST after school were associated with a higher risk of being overweight or having obesity compared with the lowest quartile. Conclusions The strategies to prevent overweight and obesity among preschool children should consider cumulative PA of any intensity during the weekend, even light PA. Moreover, decreasing screen time and playing video games after school might help prevent overweight/obesity.